The Middle East perspective of Corporate Social Responsibility - Yehia Al-Daaja; György Norbert Szabados (International Journal of Engineering and Management Sciences, 2018)
Corporate social responsibility (CSR) in the Middle East is gaining more importance than in the past. Although it still remains more about philanthropy and charity, it moves towards a more strategic approach which includes formalizing ways of giving, as a set of non-random actions, and focuses more on addressing social ills and environment, economic challenges, that are hindering development. However, the business in the region has not yet taken the step to fully integrate the CSR into their core business operations. The most common challenges that facing the CSR implementation are the lack of government requirements and incentives, spreading awareness, building CSR partnership model, going beyond the marketing and PR campaigns, and full integration of CSR into the business strategy. In this paper, we aim to introduce the current state of the CSR in the Middle East and its perspectives, besides reviewing its evaluation stages, motivations, and current challenges. Moreover, we aim to examine CSR common practices through examples from the financial sector. The research method applied in this research is based on secondary data sources and we have used desk research to illustrate most important points and findings on the topic.